Statements and silence: fanfic paratexts for ASOIAF/Game of Thrones. Issue 1 (2nd January 2016) - Fathallah, Judith
Abstract : Today, most media authors acknowledge and to some degree integrate the user-generated content of their fandom. Some, however, still perform authoritarian positions of prohibition. George R. R. Martin, the creator of A Song of Ice and Fire, attempts to ban fanfiction, whilst acknowledging he cannot control use of the characters licensed to the TV adaptation ( Game of Thrones ). Building on the work of Jonathan Gray and Alexandra Herzog on paratexts in fandom studies, this article performs a critical discourse analysis on a systematic sample of the paratexts fanfic authors attach to fanfic from a cross section of online forums. These statements discursively reconfigure constructions of authorship and ownership, strongly inflected by the factors of site, audience and category. However, these paratexts evidence a paradox, legitimating their work by reference to the authority of what is already legitimate. The more radical gesture may be the absence of paratextual justification, and refusal of the 'incitement to discourse' which Foucault recognised as a technique of modern power.